498 Downregulation of CD5 in CD8+ T tumour-infiltrating lymphocytes associates with increased level of activation and exhaustion. (10th December 2020) - Alotaibi, Faizah; Vincent, Mark; Min, Weiping; Koropatnick, James
Abstract : Background: CD5, a member of the scavenger receptor cysteine-rich superfamily, is a marker for T cells and a subset of B cells (B1a). CD5 associates with T-cell and B-cell receptors and impair TCR signaling 1 2 and increased CD5 is an indication of B cell activation. Furthermore, CD5 levels on CD8+ T cell splenocytes were significantly increased after TCR/CD3 stimulation using ex vivo treatment with anti-CD3/anti-CD28 MAbs compared to non-stimulated CD8+ T splenocytes. 3 Previous studies have shown a correlation between CD5 and anti-tumour immunity where CD5 knockout mice inoculated with B16F10 melanoma cells had delayed tumour growth compared to wild type mice. 4 In tumour-infiltrating lymphocytes (TILs) isolated from lung cancer patients, CD5 levels were negatively correlated with anti-tumour activity and tumour-mediated activation-induced T cell death, 5 suggesting that CD5 could impair activation of anti-tumour T cells. However, the correlation between CD5 level expression and T cell activation and exhaustion in the tumour microenvironment and in peripheral organs is ill-defined and requires further investigation. Methods: We determined CD5 levels in T cell subsets in different organs in mice bearing syngeneic 4T1 breast tumour homografts and assessed the relationship between CD5 and increased CD69 and PD-1 (markers of T cell activation and exhaustion) by flow cytometry. Results: We report that T cell CD5 levels were higher in CD4+ T cells than in CD8+ T cells in 4T1 tumour-bearing mice, and that high CD5 levels on CD4+ T cells were maintained in peripheral organs (spleen and lymph nodes). However, both CD4+ and CD8+ T cells recruited to tumours had reduced CD5 compared to CD4+ and CD8+ T cells in peripheral organs. In addition, CD5highCD4+ T cells and CD5highCD8+ T cells from peripheral organs exhibited higher levels of activation and associated exhaustion compared to CD5lowCD4+ T cell and CD5lowCD8+ T cell from the same organs. Interestingly, CD8+ T cells among TILs and downregulated CD5 were activated to a higher level, with concomitantly increased exhaustion markers, than CD8+CD5+ TILs. Conclusions: Thus, differential CD5 levels among T cells in tumours and lymphoid organs can be associated with different levels of T cell activation and exhaustion, suggesting that CD5 may be a therapeutic target for immunotherapeutic activation in cancer therapy. Acknowledgements: The author thanks Rene Figueredo and Ronak Zareardalan for their assistance in animal work Ethics Approval: This study was approved by the Animal Use Subcommittee of the University of Western Ontario References: Azzam HS, et al., Fine tuning of TCR signaling by CD5. The Journal of Immunology 2001. 166(9): p. 5464–5472. Voisinne GA, Gonzalez de Peredo and Roncagalli R. CD5, an undercover regulator of TCR signaling. Frontiers in Immunology 2018;9:p. 2900. Alotaibi, F., et al., CD5 blockade enhances ex vivo CD8+ T cell activation and tumour cell cytotoxicity. European journal of immunology 2020;50(5): p. 695–704. Tabbekh, M., et al., Rescue of tumor-infiltrating lymphocytes from activation-induced cell death enhances the antitumor CTL response in CD5-deficient mice. The Journal of Immunology, 2011. 187(1): p. 102–109. Dorothée, G., et al., In situ sensory adaptation of tumor-infiltrating T lymphocytes to peptide-MHC levels elicits strong antitumor reactivity. The Journal of Immunology 2005;174(11): p. 6888–6897.